Rencana Bisnis dalam Meningkatkan Usaha UMKM di Era Digitalisasi - Margolang, Ade Irvan; Silalahi, Khairul Amri; Nst, M Rezi Syahbanda (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This business plan is designed to advance Micro, Small and Medium Enterprises (UMKM) in facing the challenges and opportunities of the digitalization era. In this context, the main focus is to implement a comprehensive digitalization strategy. First, involving UMKM in online platforms to increase market visibility and reachability. Second, adopt an effective digital marketing strategy, including the use of social media, SEO and data-based campaigns. Based on technological innovation, this plan aims to have a positive impact on the growth of UMKM, depict realistic growth projections, and provide adaptation strategies to changing digital market trends. It is hoped that the steps proposed in this business plan will strengthen the competitiveness of UMKM in the digital era, creating a business environment that is sustainable and responsive to dynamic changes in the digital economy.